Efficient Synthesis of 4-Amino-2-methoxy-7,8-dihydropyrido[4,3-d]pyrimidin-5-ones: Practical Access to a Novel Chemotype in the Development of DGAT-1 Inhibitors - Bahnck, Kevin B.; Shavnya, Andrei; Tao, Yong; Lilley, Susan C.; Andrews, Melissa P.; Aspnes, Gary E.; Bernhardson, David J.; Bill, David R.; Bundesmann, Mark W.; Dow, Robert L.; Karki, Kapil; Le, Tung; Li, Qifang; Munchhof, Michael J.; Nematalla, Asaad; Nihlawi, Mohammed; Patel, Leena; Perreault, Christian; Waldo, Michael (Synthesis, 2012)
A practical access to an unprecedented, fused bicyclic 4-amino-2-alkoxy-7,8-dihydropyrido[4,3-d]pyrimidin-5-one scaffold is developed. The synthesis of the potent inhibitor, 2-{4-[4-amino-2-methoxy-5-oxo-7,8-dihydropyrido[4,3-d]pyrimidin-6(5H)-yl]phenyl}-2-methylpropanamide is detailed, with particular emphasis placed on synthetic efficiency and scalability. With the isolation of solid intermediates, the routes described offer clear elements of practicality and facilitate production of the target compound on large scale (>10 g) without chromatography.
Keywords: 4-amino-2-methoxy-7,8-dihydropyrido[4,3-d]pyrimidin-5-ones; heterocycle synthesis; DGAT-1 inhibitor; Buchwald amination; aza-Michael addition; Dieckmann-type cyclocondensation